Coupled Effects of Magnetohydrodynamics and Nanoparticles on Nonlinear Stretching Wedge Flow with Multiple Slips and Non-Uniform Heating - akinrimade, Victor Adetayo; Kolawole, Mutairu Kayode (JURNAL DIFERENSIAL, 2024)
This study investigates the complex interplay between magnetohydrodynamics (MHD), nanoparticle behavior, and fluid flow characteristics in the context of a nonlinear stretching wedge with multiple slips and non-uniform heating. The flow is driven by a water-based fluid containing nano-sized particles of aluminum oxide and copper $\left( Al_2O_3-Cu/H_2O\right)$ . The governing equations of the problem are derived and then solved using appropriate numerical techniques. The effects of various parameters such as the magnetic field strength, nanoparticle volume fraction, wedge angle, slip parameters, and non-uniform heat source are thoroughly analyzed. Results reveal significant alterations in the flow behavior due to the presence of nanoparticles and the applied magnetic field. The interaction between the fluid flow and magnetic field induces a substantial change in velocity and temperature distributions along the wedge surface. Moreover, the slip effects and non-uniform heat source further modify the flow characteristics. This investigation provides valuable insights into the coupled effects of MHD, nanoparticles, and slip conditions on the flow dynamics and thermal behavior in nonlinear stretching wedge configurations. Such insights are crucial for understanding and optimizing processes involving fluid flow and heat transfer in engineering applications, particularly those utilizing nano-fluids and magnetic fields.